Influence of corporate governance mechanisms on audit and non-audit fees: a comparison of government linked companies (GLCs) and non-GLCs / Masdiah Abdul Hamid - Abdul Hamid, Masdiah (2011)
The purpose of this study is to examine the association between fees, and board and audit committee characteristics of 191 government-linked companies (GLCs) and nongovernment linked companies (non-GLCs). Audit tenure also involved in this study in order to see the impact of fees paid on auditor independence. It is hypothesised that corporate governance practices is not affect to the auditor’s assessment, resulting no affect on the fees payment. In order to investigate the findings, a sample of 191 GLCs and non-GLCs listed on the Bursa Malaysia are used that across three years in 2006 to 2008. It is analyzed using a quantitative method that employed by SPSS which compared similar characteristics of boards and audit committee in audit fees and non- audit fees. Multiple regression analysis is used to estimate the relationships proposed in the hypotheses. The finding reveals that fees are positively and significantly related to board size, while not significant related to other governance variables for GLCs. With respect to the non-GLCs, the study reveals that board size is negatively and significantly associated with fees. The study also finds a significant negative relationship between duality role and independent audit committee with audit fees, while not significant with non-audit fees. As for audit tenure, the study reveals that fees are not significant associated with audit tenure for both GLCs and non-GLCs. As a conclusion, there is quite different result between GLCs and non-GLCs in terms of fees payment. The result also shows that GLCs pay lower fees and practice more favourable corporate governance practices compared to their non-GLCs counterparts.